دراسة مدى توافق الإطار التصوري للنظام المحاسبي المالي - شنايت, بلال; حبيش, علي (جامعة الوادي University of Eloued, 2020)
This article aims to study the degree of compatibility between the conceptualframework of the financialaccounting system SCF and the conceptualframework for financialreporting for the years 2010 and 2018, by following the descriptive approach in presenting the concepts and the inductive approach in issuingjudgmentsrelated to the comparative study, As thisstudyconcludedthat the conceptualframework for the SCF wasimplicitly and to a large extent compatible with the conceptualframework for financialreporting for the year 2010, but after the update of the conceptualframework for financialreporting in March 2018, itbecamenecessary to reconsider the conceptualframework of the Algerian financialaccounting system SCF and update it in accordance with the developments of the Conceptual Framework for Financial Reporting 2018.
Study the extent of compatibility of the conceptual framework of the financial accounting system SCF with the conceptual framework for financial reporting for the years 2010 and 2018 "a comparative study"
مقال
Keywords: This article aims to study the degree of compatibility between the conceptualframework of the financialaccounting system SCF and the conceptualframework for financialreporting for the years 2010 and 2018, by following the descriptive approach in presenting the concepts and the inductive approach in issuingjudgmentsrelated to the comparative study, As thisstudyconcludedthat the conceptualframework for the SCF wasimplicitly and to a large extent compatible with the conceptualframework for financialreporting for the year 2010, but after the update of the conceptualframework for financialreporting in March 2018, itbecamenecessary to reconsider the conceptualframework of the Algerian financialaccounting system SCF and update it in accordance with the developments of the Conceptual Framework for Financial Reporting 2018; The conceptual framework of the financial accounting system ; Conceptual framework for financial reporting ; Accounting standards ; International Accounting Standards Board IASB ; Financial reports